Phytochemical Screening and Selected Biological Activities of Solanum incanum L. Fruit Extracts - Alhadi, Fatima A.; Atta, Safia Tawfik; Ibrahim, Hassan M. (PSM Microbiology, 2025)
Numerous studies have documented the use of the fruit of Solanum incanum in traditional medicine. This study aims to investigate the phytochemical composition, antioxidant capacity, and antimicrobial efficacy of S. incanum fruit extracts. Methanolic and aqueous extracts were prepared using a rotary shaker method. Phytochemical screening revealed the presence of alkaloids, saponins, phenols, tannins, flavonoids, steroids, and carbonyl compounds in the methanol extract. In contrast, the aqueous extract possessed alkaloids, saponins, phenols, tannins, flavonoids, and carbonyl compounds. Fourier-transform infrared (FT-IR) spectroscopy analysis of the methanol extract indicated the presence of hydroxyl (–OH), aromatic/alkene (C–H), carbonyl (C=O), C=C, and C–O functional groups. However, in the aqueous extract, the FT-IR spectra showed the presence of hydroxyl (–OH), aliphatic C–H (methane group), carbonyl (C=O), amine (N–H), and C–O groups. The antioxidant activity of both extracts was assessed using the DPPH (2, 2-diphenyl-1-picrylhydrazyl) radical scavenging assay. The methanol extract exhibited significantly higher antiradical activity compared to the aqueous extract, indicating greater antioxidant potential. Antimicrobial activity was evaluated using the agar well diffusion method against three human bacterial pathogens—Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa—and one fungal pathogen, Candida albicans. The aqueous extract demonstrated superior antimicrobial activity against all tested pathogens, followed by the methanol extract. The antimicrobial efficacy of the aqueous extract is probably attributable to the presence of bioactive antimicrobial peptides (AMPs), which are essential components of the innate immune defense system in many organisms.